Analisis penerapan higiene dan sanitasi rumah makan di kelurahan Tarempa Kecamatan Siantan Kabupaten Kepulauan Anambas Analysis the application of Hygiene and Sanitation in restaurants of urban village Tarempa sub-district Siantan regency Kepulauan Anamba - Malik, Fadri Rabial; Abidin, Aldiga Rienarti; Nurlisis, Nurlisis; Hayana, Hayana; Sari, Nila Puspita (LPPM Hang Tuah Pekanbaru, 2024)
Hygiene and sanitation is a specific action to improve hygiene and health through maintaining the health of each individual and the environment that affects it. Of the several restaurants that do not meet the requirements as many as 12 restaurants. Identifiable risk factors include unhygienic food ingredients, improper processing, improper storage, contaminated equipment and people handling the food. The purpose of this study was to analyze the application of restaurant hygiene and sanitation in the Tarempa sub-district, Siantan district, Anambas Islands district in 2022. This type of research was qualitative. The research was conducted in one of the restaurants in the Anambas Islands Regency that did not meet the requirements in March 2022. There were five informants consisting of one restaurant owner, two handlers, and sanitarian staff and visitors. Collecting data using interviews and observations in restaurants that do not meet the requirements. The results showed that in the restaurant some variables did not meet the hygiene and sanitation requirements based on the Minister of Health Number 1098/MENKES/SK/VII/2003 such as not using gloves, not providing organic and inorganic waste bins and toilets that had not been separated and did not have a septic tank. The suggestion is that it is necessary to make efforts to improve the application of hygiene and sanitation in restaurants and attend special training on hygiene and sanitation requirements.